2017
DOI: 10.4236/ajibm.2017.78070
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Individual Behavior in Green Event—From the Theory of Planned Behavior Perspective

Abstract: Being an indispensable component of tourism industry, the event industry is growing rapidly over the past decades in terms of diversity, size, number and popularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Despite the research studies of Mao and Lyu (2017), Kim and Jang (2014), Amaro et al (2018), Wang (2017), our findings have not proved the importance of subjective norms on customer behaviour when using P2P accommodation. This could be caused by the observed group of millennials, which is far more open to new experiences, focused on cooperation with a comparison with older generations (Olson & Kemp, 2015).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Despite the research studies of Mao and Lyu (2017), Kim and Jang (2014), Amaro et al (2018), Wang (2017), our findings have not proved the importance of subjective norms on customer behaviour when using P2P accommodation. This could be caused by the observed group of millennials, which is far more open to new experiences, focused on cooperation with a comparison with older generations (Olson & Kemp, 2015).…”
Section: Discussioncontrasting
confidence: 82%
“…Kim and Jang (2014) refer to subjective norms as the customer's decision that is affected by social and interpersonal pressure. The individual's opinion based on what other people think also assumes importance and forecasts their intention to behave in a certain way (Wang, 2017). Moreover, latest studies (Amaro et al, 2018;Mao & Lyu, 2017) suggest that subjective norms have a positive impact on the desire to use P2P accommodation.…”
Section: Mgb Model From the Perspective Of The Millennial Generationmentioning
confidence: 99%
“…When it comes to the attitude and perceived behavior of tourists to visit mega-events, the use of TPB is considered one of the best conceptual frameworks that can explain this intention and of tourists to visit the event [22]. This theory explores the effects of three factors on intention to make a decision, including perceived behavior control, attitude and subjective norms, on the intention to make a decision, such as visiting a mega-event [23]. One of the key advantages of adopting the TPB conceptual framework is its adaptability, which means that other constructs may be added to the model to increase its predictive usefulness in a specific behavioral setting [24].…”
Section: The Theory Of Planned Behaviormentioning
confidence: 99%
“…According to Laing and Frost (2010) a green event has a sustainability policy and the event management applies sustainability practices when running its operations and processes. The sustainability standards should be met to satisfy the needs of future generations, not only the current one (Jenkins, 2010;Wang, 2017). To inspire event organisations and event managers to run events in a sustainable manner, Ahmad, Rashid, Abd Razak, Yusof, and Shah (2013) to focus on six areas: (1) Energy Efficiency (using energy star rated products, natural light and ventilation, keep electricity consumption to a minimum, etc.…”
Section: The Green Sports Event Brandmentioning
confidence: 99%
“…Besides, the Sydney 'Green Games' exemplifies the benefits of engaging stakeholders to strengthen the understanding of the various dimensions of the environmental challenges. When improving green event strategies followed by effective implementation, there are opportunities to influence green awareness and behaviour of organisers, employees, partners, visitors, and citizens benefitting the awareness of environmental protection, and the event industry (Wang, 2017). Merrilees and Marles (2011) concluded that instead of using generic checklists at a real business event, the actual applied green practices are more effective as a promotional tool for green policies intended to decrease possible environmental costs of business events.…”
Section: The Green Sports Event Brandmentioning
confidence: 99%